2018
DOI: 10.1155/2018/4560101
|View full text |Cite
|
Sign up to set email alerts
|

Studying Engineering Characteristics of Asphalt Binder and Mixture Modified by Nanosilica and Estimating Their Correlations

Abstract: e objective of this research was to investigate rutting and fatigue distresses in asphalt containing 2, 4, 6, and 8 percent of nanosilica (NC) and to find out the correlation between engineering properties of the modified binder and mixture asphalt. In order to study the effect of NC on the rutting and fatigue properties of modified binders, the multiple stress creep recovery (MSCR) and linear amplitude sweep (LAS) tests were carried out. e Marshall stability, dynamic creep, and four-point bending beam fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For 6% of NS, the Marshall flow was higher than for 2% and 4% of NS but remained 6.3% lower than the control mixture's flow. However, Hasaninia & Haddadi (2018) [29] showed that the Marshall stability and flow increase with the concentration of NS. In our study, the measured decrease in flow may be attributed to a different process of gradation and densification that increased stability but decreased flow.…”
Section: Marshall Testmentioning
confidence: 99%
“…For 6% of NS, the Marshall flow was higher than for 2% and 4% of NS but remained 6.3% lower than the control mixture's flow. However, Hasaninia & Haddadi (2018) [29] showed that the Marshall stability and flow increase with the concentration of NS. In our study, the measured decrease in flow may be attributed to a different process of gradation and densification that increased stability but decreased flow.…”
Section: Marshall Testmentioning
confidence: 99%
“…In recent years, nanomaterials have been widely used to improve the performance of asphalt binder because of its large specific surface area, high surface free energy, and good dispersion ability [9][10][11][12]. Hasaninia and Haddadi investigated the rutting and fatigue damage of asphalt caused by nano-SiO 2 and found the correlation between modified binder and the engineering performance of asphalt mixture [13]. Wu et al explored the temperature sensitivity of nanoparticles to cement mortar, the influence of nano-SiO 2 on the strength of cement asphalt mortar, and the performance of nano-SiO 2 cement asphalt mortar at different temperatures [14].…”
Section: Introductionmentioning
confidence: 99%